Factors influencing major adverse cardiac events among people with acute coronary syndrome admitted to a tertiary hospital in Northeastern Thailand: A cross-sectional study - Piwpong, Ratchanee; Plienthaisong, Bulan; Plongram, Thunsuda; Ngaosri, Wilaiwan; Narasri, Thachaiya (Belitung Nursing Journal, 2025)
Background: Acute coronary syndrome (ACS) is a severe cardiovascular condition that can lead to acute myocardial infarction (AMI), resulting in significant morbidity and elevated mortality rates. Objective: This study aimed to examine complications arising from ACS in patients admitted to a tertiary hospital and identify the influencing factors. Methods: A cross-sectional study was conducted between February and December 2021 among patients diagnosed with ACS at the tertiary hospital in Northeastern Thailand. The sample included 133 participants hospitalized for ACS. Simple random sampling was employed, with data collected from the patient registry by selecting 15 individuals at a time until the target of 1,998 patients was reached. Statistical analyses included descriptive statistics, Chi-Square test, Fisher’s exact test, and binary logistic regression to identify significant predictors of complications in this population. Results: Factors influencing the occurrence of major adverse cardiac events (MACE) included cardiac function and the need for cardiopulmonary resuscitation (CPR). Patients with New York Heart Association (NYHA) class II-IV had a significantly higher risk of MACE compared to those with NYHA class I (p <0.001; 95% CI, 2.008–10.984). Additionally, patients who received CPR were 4.15 times more likely to experience MACE than those who did not receive CPR (p <0.05; 95% CI, 1.029–16.729). Conclusions: This study demonstrated that cardiac function and the necessity for CPR significantly influence the development of MACE in patients with ACS. These findings highlight the importance of thorough evaluation and monitoring by healthcare teams during hospitalization, particularly for patients with abnormal cardiac function or a history of CPR. Prompt identification and targeted interventions for high-risk individuals can improve outcomes and reduce complications. Nurses should prioritize follow-up evaluations for ACS patients with NYHA class II-IV or those who have undergone CPR, as these individuals are at elevated risk for developing MACE.